2015
DOI: 10.1162/rest_a_00423
|View full text |Cite
|
Sign up to set email alerts
|

Learning from Teen Childbearing Experiences of Close Friends: Evidence using Miscarriages as a Natural Experiment

Abstract: We examine peer effects in teen childbearing among close friends, using miscarriages as a natural experiment. We use 775 women from the core sample of Add Health who had a friend with a teen pregnancy. We find a sizable negative treatment effect -a close friend's teen birth is associated with a 6 percentage point reduction in the likelihood of own teen pregnancy and childbearing. There is evidence that this effect operates through a learning mechanism by changing beliefs regarding early childbearing. Effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…This interest has motivated a body of recent work examining peer effects that operate via friendships (see, e.g., Fletcher and Ross ; Card and Giuliano ; Yakusheva and Fletcher ; Daw, Margolis, and Verdery ). For recent applications featuring randomly assigned, non‐roommate peer groups, see, for example, Murphy () and Booij, Leuven, and Oosterbeek ().…”
mentioning
confidence: 99%
“…This interest has motivated a body of recent work examining peer effects that operate via friendships (see, e.g., Fletcher and Ross ; Card and Giuliano ; Yakusheva and Fletcher ; Daw, Margolis, and Verdery ). For recent applications featuring randomly assigned, non‐roommate peer groups, see, for example, Murphy () and Booij, Leuven, and Oosterbeek ().…”
mentioning
confidence: 99%
“…Peers' behaviors and attitudes have also been documented to affect individuals' fertility. Perceived prevalence of sexual behaviors among peers has been found to influence early sexual initiation (Kinsman, Romer, Furstenberg, & Schwarz, ), sexual activity, condom use (Romer et al, ), and teen pregnancy (Yakusheva & Fletcher, ). Scholars have also found that young people's beliefs regarding their peers' views on the riskiness and acceptability of sex affects their rates of oral sex (Halpern‐Felsher, Cornell, Kropp, & Tschann, ) and age at first intercourse (Baumer & South, ), whereas perceptions of unfavorable peer attitudes toward intercourse have been linked to intentions to remain sexually abstinent (Watts & Nagy ) and to delay sexual initiation (for a review, see Buhi & Goodson, ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Other recent studies have tested for peer effects in different risky behaviors. One study exploiting the natural experiment of randomized roommate assignment found evidence of positive peer effects in binge drinking but no detectable peer effects in other behaviors such as smoking or drug use (Eisenberg et al, 2014), and a study that exploited the natural experiment of miscarriage found evidence of negative peer effects in teen pregnancy (Yakusheva and Fletcher, 2015). We contribute to this broader literature by exploiting the natural experiment of Mendelian randomization and focusing on the exogenously-determined peer group of full siblings.…”
mentioning
confidence: 96%